Blankets in the River with Oranges and Other Stories - Gamero, Rafael (East Carolina University, 2015)
This thesis is a collection of five short stories, four flash fiction pieces, and one creative nonfiction piece. They all have strong character perspectives and are unified by a distinctive Caribbean/Central American experience and setting in Belize. The tone of the stories also range from melancholic to satire, and the flash fiction pieces occur between each of the short stories, connecting them in setting, character, theme, or narrative style. The last story is a creative nonfiction piece that is character-based, however, still connected thematically to the rest of the collection.
Keywords: Literature; Caribbean literature; Latin American literature; Belize; Caribbean; Fiction; Latin American; Nonfiction; Short stories; Belize--Fiction; Flash fiction, American